THE EXISTENCE OF ISLAMIC PARTIES AFTER INDEPENDENCE IN INDONESIA - Amalia Dwi Fitriani; Restie Ramadhanti; Nasikhin; Fihris (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2023)
Islam is a religion that puts the principle of justice and truth to each of its adherents, Islam in the dynamics of economics, education, social, and culture in Indonesia is highly developed. But there are, challenges that occurred such as, movements at that time, occurred in various regions in Indonesia. This makes Islamic leaders in Indonesia play a role in spreading Islamic da'wah so that Islamic principles can develop. This study aims to analyze the development of Islamic parties during the period of Indonesian independence. This study uses a literature review, which produces data that; (1) Social dynamics through inter-island trade routes so that it has a major effect on Chinese, Islam and European culture as well as in terms of culture still using local customs due to cultural acculturation at the spice trade center. (2) The post-independence government system that imitated the Medina Charter at that time, (3) the existence of Indonesian Islamic political parties such as Masyumi, Tarbiyah Islamiyah Association, Indonesian Islamic Syarikat Party, and Nahdlatul Ulama. (4) Islamic da'wah strategies that develop through trade, education and arts. (5) Challenges faced by the movement of DI/TII and Islamic patterns that are not so strong in national and state life. (6) Figures who influence such as K.H Hasyim Asyari, K.H Abdul Wahid Hasyim, and Teungku Fakinah after independence in Indonesia. This study has an implication of increasing the historical literature of Indonesian Islamic civilization so as to increase the treasury of Islamic knowledge in Indonesia.